2013
DOI: 10.1016/j.diamond.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term H-release of hard and intermediate between hard and soft amorphous carbon evidenced by in situ Raman microscopy under isothermal heating

Abstract: We study the kinetics of the H release from plasma-deposited hydrogenated amorphous carbon films under isothermal heating at 450, 500 and 600 °C for long times up to several days using in situ Raman microscopy. Four Raman parameters are analyzed. They allow the identification of different processes such as the carbon network reorganization and the H release from sp 3 or sp 2 carbon atoms and the corresponding timescales. Carbon reorganization with aromatization and loss of sp 3 hybridization occurs first in 10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…Recent studies dealing with the thermal stability and long term hydrogen release of a-C:H layers [6,7] have allowed to investigate how useful information, such as structure evolution and hydrogen release, can be retrieved from Raman spectra. It is known that Raman spectroscopy is a powerful tool to characterize C-based materials that contain sp 2 carbon atoms (C(sp 2 )) such as graphite, graphene, nanotubes, soots, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies dealing with the thermal stability and long term hydrogen release of a-C:H layers [6,7] have allowed to investigate how useful information, such as structure evolution and hydrogen release, can be retrieved from Raman spectra. It is known that Raman spectroscopy is a powerful tool to characterize C-based materials that contain sp 2 carbon atoms (C(sp 2 )) such as graphite, graphene, nanotubes, soots, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, we have shown that the parameters  G and  G are mainly sensitive to the structural changes such as the re-organization leading to a larger aromatization, and the loss of C(sp 3 ) induced by heating. In [6], we have evidenced the long term kinetics of the isothermal H release from a-C:H layers with different initial H/H+C ratios and various thicknesses, at temperatures of 450 °C, 500 and 600 °C. We have shown how the kinetic evolution (fast regime followed by a slower one) provides valuable information on the H release processes and emphasizes the role of the initial structure and H-content on these processes:the higher the initial H content, the faster the kinetics, in agreement with what is known on the instability of this type of hydrogenated layers.…”
Section: Introductionmentioning
confidence: 99%
“…Except the resonance effect which was not studied by Pena-Alvarez et al [223], exactly all these effects have been observed in stressed nanocones as can be seen in Figure 16. In this figure, we compare the width of the G band (Г G ) versus I D /I G scaled by the laser wavelength (λ 0 ) for the large variety of samples analyzed by Pardanaud et al [66], (referred here to "disordered carbons"), heated amorphous carbons (work of Pardanaud et al [225,226]), bombarded graphite (work of Niwase et al [227]) and the nanocones from the work of Pena-Alvarez et al [223]. The grey lines are the models based on the Tuinstra and Ferrari relations (see the work of Pardanaud et al [66], for more details) and stand for disordered graphite and amorphous carbons, respectively.…”
Section: Nanoconesmentioning
confidence: 99%
“…The time evolution of these parameters is used in Fig. 4e and 4f to derive the H content [19,20,36] and the dispersion curve of the G band [26,27]. In Fig.…”
Section: Raman and Eels Spectramentioning
confidence: 99%
“…The proper characterization of the hydrogen content together with the sp 2 fraction is thus of particular importance. These coatings need also to be thermally stable and changes in a-C:H local chemistry during thermal annealing have then regained an interest these last few years [3,4,[12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%